2022
DOI: 10.1128/spectrum.00610-22
|View full text |Cite
|
Sign up to set email alerts
|

AI-2/LuxS Quorum Sensing System Promotes Biofilm Formation of Lactobacillus rhamnosus GG and Enhances the Resistance to Enterotoxigenic Escherichia coli in Germ-Free Zebrafish

Abstract: Lactobacillus rhamnosus GG is a widely used probiotic to improve host intestinal health, promote growth, reduce diarrhea, and modulate immunity. In recent years, the bacterial quorum sensing system has attracted much attention; however, there has not been much research on the effect of the LuxS/AI-2 quorum sensing system of Lactobacillus on bacteriostasis, microbial ecology balance, and immune regulation in intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Furthermore, the direct binding between LuxS and dronedarone was verified by an SPR experiment. LuxS is an important component of the type II QS system Luxs/AI-2, which mainly uses AI-2 as a signaling molecule to mediate interspecies communication. , In this system, LuxS acts as an S-ribosylhomocysteinase, which catalyzes the cleavage of the thioether linkage of S-ribosylhomocysteine to produce 4,5-dihydroxy-2,3-pentanedione, which can rearrange to R- or S -2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran (R- or S-THMF), both better known as AI-2 . Previous studies have shown that LuxS/AI-2 is involved in biological processes such as biofilm formation, conjugation, virulence, and antibiotic resistance. , Therefore, it is reasonable to believe that dronedarone affects the function of the QS system by inhibiting LuxS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the direct binding between LuxS and dronedarone was verified by an SPR experiment. LuxS is an important component of the type II QS system Luxs/AI-2, which mainly uses AI-2 as a signaling molecule to mediate interspecies communication. , In this system, LuxS acts as an S-ribosylhomocysteinase, which catalyzes the cleavage of the thioether linkage of S-ribosylhomocysteine to produce 4,5-dihydroxy-2,3-pentanedione, which can rearrange to R- or S -2-methyl-2,3,3,4-tetrahydroxytetrahydrofuran (R- or S-THMF), both better known as AI-2 . Previous studies have shown that LuxS/AI-2 is involved in biological processes such as biofilm formation, conjugation, virulence, and antibiotic resistance. , Therefore, it is reasonable to believe that dronedarone affects the function of the QS system by inhibiting LuxS.…”
Section: Discussionmentioning
confidence: 99%
“…QS system of bacterium has aroused widespread discussion, but less research has been done on the regulation of LuxS/AI-2 QS system on Lactobacillus in gut health. In previous studies, we have demonstrated that the production of AI-2 signaling molecules decreased significantly after luxS deletion from both qualitative and quantitative perspectives by using BB170 strain and high performance liquid chromatography (HPLC), respectively ( 15 ). In this study, we selected newborn piglets with similar body weight and fed LGG or its mutant to them by orally administration immediately after birth.…”
Section: Discussionmentioning
confidence: 99%
“…As AI-2 produced by one species could affect gene expression in another, this feature makes AI-2 to act an excellent candidate for mediating cell-cell interactions in the mammalian gut. In a previous study we have found that deficiency of the LuxS/AI-2 QS system reduced LGG AI-2 activity, interbacterial adhesion and biofilm formation (15). Based on studies of bacterial cell interactions in laboratory systems, it is likely that the exchange of these signals plays a critical role in the dense bacterial communities exist in the mammalian gut (16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, positive regulation of intestinal probiotic QS (such as AI-2/LuxS QS system of Lactobacillus rhamnosus GG) can promote the formation of probiotic biofilms, thus strengthening the immune functions of the intestinal barrier and promoting intestinal health. [84,164] (2) optimizing the bacterial population structure: positively regulating the QS of targeted microbiota (such as AnAOB and starter bacteria) can regulate the bacterial population structure and increase the abundance of the targeted microbiota, which has great application potential in the field of biodegradation and microbial fermentation. [80,165] (3) visualization of bacterial virulence activities: by amplifying and transforming the QS signal of pathogenic bacteria in clinical samples or food into visualized signals, the virulence activities of pathogenic bacteria can be reflected dynamically; thus, the sensitivity of bacterial detection techniques can be greatly improved.…”
Section: Positive Signal Reinforcementmentioning
confidence: 99%